Analisis pengelolaan zakat fitrah oleh panitia zakat perspektif UU Nomor 23 Tahun 2011 tentang Pengelolaan Zakat: Studi di Dusun Biting Desa Gonggang Kecamatan Poncol Kabupaten Magetan - Muhroni, Tedy (Maliki Interdisciplinary Journal, 2024)
Zakat management is a series of important processes in zakat. In society, there are still many practices of managing zakat that do not comply with the regulations. This paper aims to analyze the management of Zakat Fitrah by the Zakat Commission using the perspective of the Act No. 23 Year 2011 on Zakat Management. The study was conducted in Dusun Biting, Gonggang Village, Poncol district, Magetan district. The results of the writing showed that the management of Zakat Fitrah by the Zakat committees in Biting Dusun, Gunggang Village and Poncol District still follow the local tradition and is not fully in accordance with the provisions of the Law No. 23 Year 2011 on Zakat Management. This is due to the lack of education and the low level of public knowledge about Zakat management is still good and is in conformity with the terms of the Islamic Charter and the Law no. 23 Years 2011 on zakat management.